2019
DOI: 10.1016/j.apenergy.2019.04.161
|View full text |Cite
|
Sign up to set email alerts
|

Ignition dynamics of DME/methane-air reactive mixing layer under reactivity controlled compression ignition conditions: Effects of cool flames

Abstract: A study of ignition dynamics in a turbulent dimethyl ether (DME)/methane-air mixture under Reactivity Controlled Compression Ignition (RCCI) conditions was conducted using direct numerical simulation. Initially, the directly-injected DME and in-cylinder premixed methaneair mixture are partially mixed to form a mixing layer in between. A reduced DME/CH4 oxidization mechanism, consisting of 25 species and 147 reaction steps, is developed and validated. Ignition is found to occur as a two-stage process. Low-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Once ignited, the kernels grow rapidly, coupled with the growth of the existing burning surface (developed by edge-flame propagation). In the DNS of the two-stage ignition process, the location of the low-temperature autoignition may first be initiated in the fuel-lean part of the dimethyl ether (DME)/air mixture [135], at the stoichiometric mixture [136] or on the fuel-rich side of the DME/methane/air mixture [137]. The subsequent steps are similar in the two mixtures, which consist For turbulent spray flames in more realistic configurations, the interactions between the local flow, spray, and chemistry are even more complex [37,61,62], which have not been fully understood.…”
Section: Two-stage Ignition Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Once ignited, the kernels grow rapidly, coupled with the growth of the existing burning surface (developed by edge-flame propagation). In the DNS of the two-stage ignition process, the location of the low-temperature autoignition may first be initiated in the fuel-lean part of the dimethyl ether (DME)/air mixture [135], at the stoichiometric mixture [136] or on the fuel-rich side of the DME/methane/air mixture [137]. The subsequent steps are similar in the two mixtures, which consist For turbulent spray flames in more realistic configurations, the interactions between the local flow, spray, and chemistry are even more complex [37,61,62], which have not been fully understood.…”
Section: Two-stage Ignition Mechanismmentioning
confidence: 99%
“…However, it is noteworthy that the pre-ignition oxidative reactions of the premixed methane-air mixture before the injection of n-heptane will induce an increase in ambient temperature and produce intermediate radicals, which finally promote n-heptane ignition [227]. Furthermore, the two-stage ignition process in turbulent spray flame under dual-fuel engine-like conditions, in which DME was injected into a methane-air mixture [136,137], was investigated. In these studies, a reduced DME/CH4 oxidization mechanism with 25 species and 147 elementary reactions was incorporated.…”
Section: Turbulent Spray Flames In Dual-fuel Enginesmentioning
confidence: 99%
“…Dimethyl ether (DME) is regarded as a potential new fuel in the future due to a wide range of sources. Soot is less generated during combustion due to the absence of the carbon–carbon bond in the molecular structure. These characteristics have attracted great attention, especially using the counterflow configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analysis of DME addition to boost the overall reaction activity and combustion rate was carried out with the assistance of the heat release rate, species profiles, and reaction pathway sensitivity. The superior atomization and ignition performance of the DME has enabled it to be extensively investigated in the compression ignition (CI) engine field as well. The homogeneous compression ignition (HCCI) for various proportions of DME/H 2 and DME/CH 4 blend fuels had been investigated through the numerical simulation by Wang et al It was found that the ignition delay times of the two blends at 900 K demonstrated an inverse relation to the DME blending ratio. Furthermore, the ignition delay time of DME/CH 4 invariably exceeded that of DME/H 2 due to the stability of CH 4 molecular structure, whereas the delayed ignition time of the two blends presented opposite outcomes along with the decreasing amount of DME blend ratio at 1400 K. Park et al comprehensively evaluated a biogas/DME-blended diesel combustion process for various performance indexes, such as the pressure pulsation, heat release rate, ignition delay, combustion emissions, etc.…”
Section: Introductionmentioning
confidence: 99%